2011
DOI: 10.3324/haematol.2011.050336
|View full text |Cite
|
Sign up to set email alerts
|

Association between hemolysis and albuminuria in adults with sickle cell anemia

Abstract: We have investigated renal function and markers of hemolysis in a cohort of 424 adult African-British patients with sickle cell disease. While significant associations were found in HbSS and HbSb 0 (sickle cell anemia) patients with and without controlling for covariates between hemolytic markers and albuminuria, the associations were not significant in patients with HbSC. Estimated glomerular filtration rate, a marker of renal function, correlated significantly with reticulocyte count and bilirubin. Alpha tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
74
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 23 publications
9
74
0
Order By: Relevance
“…Thus, intravascular hemolysis represents an intrinsic mechanism for human vascular disease that manifests clinical complications in sickle cell disease and other chronic hereditary or acquired hemolytic anemias. (24)(25)(26). In contrast, as mentioned earlier, other complications were associated with lower hemolysis rates and higher steady-state hemoglobin levels, including the rate of vaso-occlusive painful episodes, ACS, and osteonecrosis (Table 1).…”
Section: Introductionmentioning
confidence: 50%
“…Thus, intravascular hemolysis represents an intrinsic mechanism for human vascular disease that manifests clinical complications in sickle cell disease and other chronic hereditary or acquired hemolytic anemias. (24)(25)(26). In contrast, as mentioned earlier, other complications were associated with lower hemolysis rates and higher steady-state hemoglobin levels, including the rate of vaso-occlusive painful episodes, ACS, and osteonecrosis (Table 1).…”
Section: Introductionmentioning
confidence: 50%
“…The increase in total hemoglobin observed with HQK-1001 merits further evaluation as higher hemoglobin levels in SCD have been associated with fewer central nervous events, such as silent brain infarcts, and lower hemoglobin levels are associated with worse cognitive function in adults [38]. Furthermore, higher hemoglobin levels and decreased hemolysis have been associated with less vasculopathy and less albuminuria in SCD [39,40]. Based on the encouraging results of the present study, a multi-national placebo-controlled Phase II study was initiated in 2012 to determine if HQK-1001 administered as single agent at 30 mg/kg daily, for a longer period of time, results in higher Hb F response than seen in this study and would support the conduct of a large phase 3 study in SCD.…”
Section: Discussionmentioning
confidence: 99%
“…3,5 In our patient cohort, both the incidence and degree of microalbuminuria are much lower in adults with HbSC disease when compared with HbSS or HbSb 0 . 6 Indeed, all our patients with HbSC disease and eGFR ,45 mL/min per 1.73 m 2 have a second renal diagnosis to account for their CKD, as in case 1. The other 2 major genetic modifiers are fetal Hb (HbF) levels and a-globin genotype.…”
Section: Natural History Epidemiology and Genetic Modifiersmentioning
confidence: 99%
“…In their cohort of 725 HbSS patients, Powars et al observed that no patient with .20% HbF had renal insufficiency. 1 Coinheritance of a thalassemia, present in 30% to 35% of SCD patients of African descent, delays the onset of microalbuminuria, 6 an effect ascribed to the ensuing reduction in hemolysis and complications related to nitric oxide-depleted vasculopathy.…”
Section: Natural History Epidemiology and Genetic Modifiersmentioning
confidence: 99%